Sanctifying texts, transforming rituals : encounters in liturgical studies : essays in honour of Gerard A.M. Rouwhorst - Rouwhorst, Gerard.; Geest, Paul van. (Brill's Studies in Catholic Theology, 2017)
Sanctifying Texts, Transforming Rituals: Encounters in Liturgical Studies explores the dynamics of Christian ritual practices in their relation to a broader cultural framework. The nineteen essays, written in honour of the liturgist Gerard A.M. Rouwhorst (Tilburg University), study liturgical developments in times of transition, in which religious and cultural changes set the development of worship practices in motion. The chapters in the first part (Texts) concentrate on the close connection between narrative texts and liturgical practice. In part two (Rituals), the focus shifts to the significance of liturgy as it expresses itself in rituals, and to the understanding of ritual acting. This section includes a variety of ritual aspects of liturgy, including the performance of the sacraments and the persons involved, as well as the relation between the liturgical ritual and material objects, such as images and relics. Section three (Encounters) crosses the borders of the discipline of liturgical studies. This final section of the book studies (ritual) relations between Christians and non-Christians through history, and includes contributions that study the dialogues between different liturgical languages and media. Contributors are: Elizabeth Boddens Hosang, Paul Bradshaw, Harald Buchinger, Charles Caspers, Paul van Geest, Bert Groen, Martin Klöckener, Bart Koet, Clemens Leonhard, Ruben van Luijk, Gerard Lukken, Daniela Müller, Willemien Otten, Marcel Poorthuis, Paul Post, Ilia Rodov, Els Rose, Joshua Schwartz, Louis van Tongeren, and Nienke Vos.